2022
DOI: 10.33369/jp2ms.6.2.286-297
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Kesalahan Peserta Didik Dalam Menyelesaikan Soal Uraian Aritmetika Sosial

Abstract: Penelitian ini bertujuan untuk mendeskripsikan jenis-jenis kesalahan serta faktor-faktor penyebab yang dilakukan peserta didik dalam menyelesaikan soal uraian aritmetika sosial. Jenis penelitian ini adalah kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan menggunakan tes diagnostik dan wawancara diagnostik. Subjek penelitian ini ialah kelas VII-B SMP Negeri 11 Kota Bengkulu yang berjumlah 29 peserta didik. Hasil penelitian menunjukkan bahwa: 1) jenis-jenis kesalahan yang dilakukan peserta did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, difficulties and mistakes in solving problems often occurred. For example, a study by Epran et al (2022) found four mistakes that students made when completing social arithmetic descriptions. There were conceptual errors, lack of understanding of the meaning of the matter due to language interpretation, failure to solve problems with correct and correct steps, as well as calculation errors.…”
Section: Introductionmentioning
confidence: 99%
“…However, difficulties and mistakes in solving problems often occurred. For example, a study by Epran et al (2022) found four mistakes that students made when completing social arithmetic descriptions. There were conceptual errors, lack of understanding of the meaning of the matter due to language interpretation, failure to solve problems with correct and correct steps, as well as calculation errors.…”
Section: Introductionmentioning
confidence: 99%